Empirical Research Regarding the Organizational Communication Performance in the Romanian Tourism Units - State, Cristina; Marei (Ozarchievici), Raluca; Dinu, Alina (European Journal of Sustainable Development, 2018)
Organizational communication, a highly debated and priority topic at a declarative-theoretical level, is extremely important when it comes to increasing the overall effectiveness of every company’s activity. Our scientific research was prompted by the fact that until the present day no study has been undertaken in an area as complex as organizational communication. It is a well-known fact that organizational communication is one of the essential factors in shaping the company culture. Within this context, we aimed at analyzing several aspects referring to the way in which organizational communication takes place and to formulate proposals which would contribute to improving the management of this activity in tourism units in Romania. The research study was undertaken over more than two years, between 2014 and 2017. We interviewed 2478 people, current and/or former customers of tourism agencies in Romania, as well as 1408 tourism agency managers, with the help of two crowdsourcing platforms goo.gl/sgzjU and goo.gl/sgzjU respectively. The results were interpreted econometrically, using the SPSS for Windows and ANOVA programs. Finally, we have formulated several conclusions and proposals, including two models of organizational communication in tourism in Romania (at macro- and at micro- level). Keywords: digital era, crowdsourcing, customer, tourism, hospitality and leisure industry JEL Codes: M20, Z30